The Lousing Method to Increase Students Learning Motivation in Learning English - Mohammad Sofyan Adi (International Journal of English Education and Linguistics (IJoEEL), 2022)
This study aims to know the effectiveness of the lousing method in increasing the motivation to learn English in the seventh-grade students of MTs Nurul Jadid. This study used a pre-experimental design using one group pre-test and post-test. Based on the results of the pre-test with a value of 32.77 and a post-test value of 67, it was proven that the post-test value is greater than the pre-test value. Meaning, there is an increase in student learning motivation. While, the results of the t-test (40.575) > t-table (2.060) indicates that H0 is rejected and H1 is accepted. Meaning, the lousing method is very effective in increasing students' motivation to learn English. This is also evidenced by the results of observations which show that students always enjoy, are active, have energy, feel happy, interactive in class and focus on the material. Therefore, the use of the lousing method really effective to be enthusiastic in learning English in a good and fun.